The comparison of Anger and Sense of Guilt in Individuals with Major Depres-sion Disorder (MDD) and Post Trau-matic Stress Disorder (PTSD) with the Normal people - M. Rajabi; R. Roshan; H.R. Jamilian (روانشناسی بالینی و شخصیت, 2013)
The aim of this study is comparison of anger and sense of guilt in people with Major Depression Disorder (MDD) and Post Traumatic Stress Dis-order (PTSD) with the normal people. The statistical population of this research includes all people with Major Depression Disorder (MDD) and Post Traumatic Stress Disorder (PTSD) who have come to Arak psy-chology health centers in 1387. Statistical population of normal people includes all staffs and employees in Arak psychology health centers. Sample of this research contains 30 people with Major Depression Dis-order (MDD), 30 persons with Post Traumatic Stress Disorder (PTSD), and 30 normal people as comparison group (totally 90 people). The in-struments were the State and Trait Anger Expression Inventory (STAXI-2) and Test Of Self – Conscious Affect - 3(TOSCA 3) questionnaires. The data of the all questionnaires were analyzed with analysis the one way Variance method using SPSS software. The taken results of this re-search showed that there is a difference between criterion of anger in people with PTSD and MDD in comparison with the normal people and the difference was significant in all the 3 groups (P 0 . 001). But there were some significant differences be-tween people of PTSD and normal people as well as between people of MDD and normal people (P <0.001).